COUPLED COMMON FIXED POINT THEOREMS OF CIRIC TYPE G-WEAK CONTRACTIONS WITH CLRG PROPERTY - Babu, G. V. R.; Subhashini, P. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2012)
In this paper we introduce property (E. A) in the context of coupled fixed points and define Ciric type g-weak contractions and prove the existence of coupled common fixed points for a pair of w-compatible maps using property (E. A). Further, we consider a pair of maps satisfying an implicit relation with property (E. A) and prove the existence of coupled common fixed points. The results of Long, Rhoades and Rajovic[16] and our results are independent. Examples are provided to illustrate this phenomenon.